Assessment of Bacillus thuringiensis var. kurstaki (Bt-127) SC formulation as a component of IPM in soybean through farmer's participatory approach: ASSESSMENT OF BT-127 SC FORMULATION AS A COMPONENT OF IPM IN SOYBEAN - P DURAIMURUGAN; P S VIMALA DEVI (Journal of Oilseeds Research, 2021)
Insect pests are major biotic constraints limiting soybean production and quality. Soybean growers rely heavily on synthetic chemical insecticides to combat insect pests. Increasing concern for environmental awareness about the use of chemical insecticides has sparked interest in eco-friendly pest management alternatives. An experiment was conducted to assess Bt-127 suspension concentrate (SC) formulation as a component of IPM under real farm situation in Hegdoli village of Kotgiri Mandal, Nizamabad District, Telangana during kharif 2017-18. Incidence of semiloopers (Chrysodeixis acuta and Mocis undata) and tobacco caterpillar (Spodoptera litura) was lowered by 99.5% and 92.9% with the first spray of Bt-127 SC formulation while their incidence was lowered by 99.6% and 97.3%, respectively in farmer's practice with spray of emamectin benzoate. After second spray of Bt-127 SC formulation, incidence of S. litura was lowered by 91.3% and found on par with 91.5% lowering from spray of chlorantraniliprole in farmer's practice. Incidence of natural enemies in IPM field after first and second spray was higher at 0.84 and 0.72 per meter row length in comparison to 0.12 and 0.40, respectively in farmer's practice. The IPM module resulted in higher cost-benefit ratio (1: 2.36) as compared with farmer's practice (1: 1.61).